Guidance and Counselling to improve Work Ethic on Lecturer Performance - Elihami Elihami (Universitas Muhammadiyah Enrekang, 2022)
Since 2016, the Sinta database is regularly covering the publication of the lectures in Muhammadiyah institutions, south Sulawesi. Six years of continuous and successful journey motivated us to celebrate its contribution through the 1st comprehensive bibliometric study. For simplicity of the publications are provided from lectures publication by indexed Sinta. From 2020 to 2021, the total number of publications (TP) were found to be (1391), total by Scopus indexed (454) and total by accreditation sinta indexed (937). The study proposed to investigate by six years of Islamic Work Ethic on lecture-performance in Muhammadiyah Education Charities in South Sulawesi. The influence of Islamic work ethic on work outcomes (research publication in Sinta, Muhammadiyah Institution commitment and job satisfaction). The sample consisted of 1.219 sinta authors from 11 Muhammadiyah institutions in South Sulawesi, Indonesia. The results suggest that the Islamic work ethic positively contributes to the effect of the Islamic work ethic on lecture-performance in Muhammadiyah Education Charities.